Strategi Guru Qira’atul Kutub Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Melalui Pembelajaran Kitab Taqrib Di MTs Al-Anwar Sarang - Rizkiyatul Aliyah; Indah Suciani (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This study aims to describe the strategies of Qira'atul Kutub teachers in improving students' critical thinking skills through Taqrib learning at MTs Al-Anwar Sarang. This study used a qualitative approach with descriptive field research. The research subjects included the principal, Qira'atul Kutub teachers, and ninth-grade B students. Data were collected through observation, interviews, and literature review, then analyzed using the interactive model of Miles and Huberman (1994). The results showed that teachers implemented two main methods: the classical Sarang method and the Madurese al-Asa method, which synergistically fostered students' analytical, reflective, and argumentative thinking skills. Teacher strategies, including text guidance, reflective discussions, and comparative analysis assignments, proved effective in improving students' critical thinking and active participation. This research confirms that the integration of traditional and modern approaches in the teaching of yellow books plays a significant role in the development of higher-order thinking skills (HOTS) in Islamic educational environments.